Mboshi and Teke Culture Contact: A Case Study of Making up Bantu Cultural Area - ITOUA, Joseph (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> This paper is based on a comparative study of three ethnic groups by focusing on the elements of interpenetration between two different civilization groups in Congo-Brazzaville namely Ngala and Teke. By so doing, the article resorts to three peoples namely Mbosi and Moye for the Ngala group and Engugwέl people for the Teke group to establish the existence of a cultural area uniting these two groups that share the same geographical space. This comparative study scrutinizes the elements of culture and history of every group that gets Ngala and Teke closer by their resemblance and reciprocal exchange beyond the gap between these two big entities. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->